Assessing self-awareness in career choice decisions among prospective Engineering students - Mangné Kardos, Zita; Kovács, Éva (Civilia, 2022)
Choosing a degree programme in higher education is one of the most important milestones in our lives. At this age, many people already have an occupation, but most of them have a school-leaving certificate attesting to the completion of a general secondary education. To facilitate this choice, the National Curriculum provides for career guidance as an important area for development in both primary and secondary education. The role of school is indisputable in further education and successful participation in the labour market. Interest and self-awareness play a key role in motivation to learn and reducing early school leaving. The success of a career choice decision is largely determined by career maturity (Rókusfalvy, 1969), the lack of which can result from a lack of adequate self-awareness (Zakar, 1988). They can also lead to overall career uncertainty (Völgyesy, 1976). In our research, we attempted to assess whether high school graduates interested in tertiary-level technical education made a decision that was appropriate to their orientation, self-awareness, and career knowledge. The study presents the results of a survey among high school graduates interested in technical education at the University of Pécs. One important aspect of the questionnaire used for the measurement was to assess the socio-economic status of the survey participants, their chosen degree programmes, their motivations for choosing a major and an institution. The other important aspect was to present a comparative study of different production fields, such as interests, work environments, job knowledge by using Holland's Code and Super's Work Values Inventory questionnaires.
Keywords: Career choice decision; Self-awareness; Interest; Technical higher education; Career orientation